2021
DOI: 10.1101/2021.02.23.432522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinatorial transcription factor profiles predict mature and functional human islet α and β cells

Abstract: Islet-enriched transcription factors (TFs) exert broad control over cellular processes in pancreatic α and β cells and changes in their expression are associated with developmental state and diabetes. However, the implications of heterogeneity in TF expression across islet cell populations are not well understood. To define this TF heterogeneity and its consequences for cellular function, we profiled >40,000 cells from normal human islets by scRNA-seq and stratified α and β cells based on combinatorial TF e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…In human α cells, variations in electrophysiologic properties, specifically capacitance and Na + currents, correlate with higher expression of α cell maturity markers and secretory genes as well as downregulation of ER stress markers (Camunas-Soler et al 2020). This observation is further supported by work from our own group, in which we showed that human α cells co-expressing the TFs MAFB and ARX had higher expression of genes involved in nutrient sensing and glucagon secretion, while α cells expressing neither TF had upregulated stress response genes (Shrestha et al 2021).…”
Section: Journal Of Endocrinologysupporting
confidence: 72%
See 1 more Smart Citation
“…In human α cells, variations in electrophysiologic properties, specifically capacitance and Na + currents, correlate with higher expression of α cell maturity markers and secretory genes as well as downregulation of ER stress markers (Camunas-Soler et al 2020). This observation is further supported by work from our own group, in which we showed that human α cells co-expressing the TFs MAFB and ARX had higher expression of genes involved in nutrient sensing and glucagon secretion, while α cells expressing neither TF had upregulated stress response genes (Shrestha et al 2021).…”
Section: Journal Of Endocrinologysupporting
confidence: 72%
“…Select human α cell identity markers from single-cell RNA-sequencing studies.All genes in this list are detected in human α cells from two or more independent studies(Wang et al 2016, Xin et al 2016, Enge et al 2017, Shrestha et al 2021, Gurp et al 2022, Tritschler et al 2022. Protein classes are reported via the PANTHER Classification System (www.pantherdb.org), with italicized entries inferred by the authors when no annotation was available.…”
mentioning
confidence: 99%
“…These TFs are not often co-expressed in human tissues, the exception being testes, islets, and skeletal muscle ( Supp Figure 6 ). In these unusual circumstances, MAFA and MAFB presumably act in a heterodimer complex, which has been linked with the most active human islet β cell population (Shrestha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal β-cells are characterized by increased expression levels of cell cycle inhibitors such as Cdkn2a and a decreased expression of cell cycle activators, including FoxM1 , cyclins, and cyclin-dependent kinases ( Avrahami et al, 2015 ; Golson et al, 2015 ; Tschen et al, 2017 ). At the same time, the population of proliferating β-cells shares similarities with immature β-cells in terms of gene expression ( Nasteska et al, 2020 ; Shrestha et al, 2021 ). For example, when proliferation in the β-cells of adult transgenic mice was induced by exogenous expression of MYC proto-oncogene (Myc ), these β-cells showed a reduced expression of genes important for GSIS SLC 2 A 2, proprotein convertase subtilisin/kexin type 1 ( PCSK 1), as well as transcriptional markers of mature β-cells: Pdx 1, MafA , and Nkx 2.2 ( Puri et al, 2018 ).…”
Section: Regeneration Of the Pancreasmentioning
confidence: 99%